Fontes de Rendimento das Famílias Rurais e a Segurança Alimentar em Cabo Verde - Victor Reis (Cadernos de Estudos Africanos)
The geo-climatic conditions of Cape Verde are extremely adverse to agriculture and therefore a major cause for the high dependency on food imports and vulnerability to prices dictated by international markets. The rise in food prices increases the difficulties of access to food and the risk of food insecurity for families. This paper seeks to identify the local factors of resilience that enable Cape Verde to deal with rising international food prices and the responses of rural households. One of the practices to address the adverse agricultural conditions is the diversification of sources of income. These sources include emigrant remittances that show the strong family ties of migrants, especially in families with weaker agricultural resources and in female headed households.